Post Reforms Growth of India’s Foreign Trade - Reenu (Journal of Commerce and Trade, 2009)
This paper is based on the growth and structure of India’s foreign trade since 1991. India’s trade has increased significantly in the post reform period. In absolute terms, the trade volume rose from US 42.2 billion ( 18.1 billion exports and 24.1 billion imports) in 1990-91 to US 391.42 billion 155.51 billion exports and 235.91 billion imports)2007-08. Exports are the major focus of India’s trade policy. The incentives offered by the export promotion package are comparable to that of any other country. The exports cover a wide range of traditional and non-traditional items while imports consists mainly of capital goods, petroleum products, raw material and chemicals to meet the ever-increasing needs of a developing and diversifying economy.